2016
DOI: 10.1074/jbc.m115.672220
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-424 Predicts a Role for β-1,4 Branched Glycosylation in Cell Cycle Progression

Abstract: MicroRNA regulation of protein expression plays an important role in mediating many cellular processes, from cell proliferation to cell death. The human microRNA miR-424 is up-regulated in response to anti-proliferative cytokines, such as transforming growth factor ␤ (TGF␤), and directly represses cell cycle progression. Our laboratory recently established that microRNA can be used as a proxy to identify biological roles of glycosylation enzymes (glycogenes). Herein we identify MGAT4A, OGT, and GALNT13 as targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 47 publications
(62 reference statements)
1
41
0
Order By: Relevance
“…Mechanistic studies from cell lines and animal model with regard to miR‐424 have identified several down‐stream targets or signaling pathways/axes in cancers, including Akt3/E2F3 and c‐Myc in HCC, DNMT1 in bladder cancer , MGAT4A , E2F7 in endometrial carcinoma, BCR‐ABL in chronic myeloid leukemia , and EMT–MET axes in breast cancer . Mechanistically, we for the first time identified that YAP1 was a direct down‐stream target of miR‐424‐3p.…”
Section: Discussionmentioning
confidence: 81%
“…Mechanistic studies from cell lines and animal model with regard to miR‐424 have identified several down‐stream targets or signaling pathways/axes in cancers, including Akt3/E2F3 and c‐Myc in HCC, DNMT1 in bladder cancer , MGAT4A , E2F7 in endometrial carcinoma, BCR‐ABL in chronic myeloid leukemia , and EMT–MET axes in breast cancer . Mechanistically, we for the first time identified that YAP1 was a direct down‐stream target of miR‐424‐3p.…”
Section: Discussionmentioning
confidence: 81%
“…MiR-424 targeted N -acetylglucosaminyltransferase that predicted a role for β -1,4 branched glycosylation in cell cycle progression in multiple mammary epithelial cell lines. 32 MiR-199a targeted ST ST6GAL1 that added an 2, 6-linked sialic acid to the termini of N -linked glycans, and reduced its expression and the sialylation of Necl-2. 33 MiR-200a targeted mRNA levels of ST ST3GAL3 and ST3GAL4, which potentially involved in antithrombin sialylation.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA regulate biological pathways by regulating sets of gene transcripts. Multiple laboratories have demonstrated that downregulation of single glycogene (or other gene) targets of miRNA mimic the biological effects of the miRNA [3133]. Thus, miRNAs could be used as a proxy to identify glycosylation enzymes involved in the pathways they regulate (miRNA proxy approach) [32,33].…”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
“…Multiple laboratories have demonstrated that downregulation of single glycogene (or other gene) targets of miRNA mimic the biological effects of the miRNA [3133]. Thus, miRNAs could be used as a proxy to identify glycosylation enzymes involved in the pathways they regulate (miRNA proxy approach) [32,33]. The miRNA proxy approach has been applied to identify functionally relevant glycogenes impacting cell states like epithelial-to-mesenchymal transition (EMT) [32] and the cell cycle [33].…”
Section: Multi-level Regulation Of Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation